2021
DOI: 10.1371/journal.pone.0261073
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of leucocyte elastase-generated cross linked fibrin degradation products (E-XDP) are elevated in chronic venous disease

Abstract: Patients with chronic venous disease (CVD) have elevated levels of leucocyte elastase (LE) released from the activation of leucocytes. In acute deep venous thrombosis (DVT), LE can degrade fibrin from the thrombus resulting in cross-linked fibrin degradation products (E-XDP) being released into the bloodstream. In patients with CVD the levels and significance of circulating E-XDP are unknown. We aimed to investigate the association between plasma E-XDP concentration and severity of CVD. Levels of E-XDP were qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…4 Sinabulya et al concluded that plasma LE-generated cross-linked fibrin degradation products were high in CVD patients, and that these levels increased as the severity of the disease increased. 13 Budzyn-Napierala et al, in their study examining LE activity, concentration, and AAT activity according to the clinical severity of the disease, indicated that LE activity decreased, particularly in the patient group with mild clinical symptoms, and that this decrease was associated with increased AAT activity. They believed that the LE-AAT balance might have turned in favor of antiprotease in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 98%
“…4 Sinabulya et al concluded that plasma LE-generated cross-linked fibrin degradation products were high in CVD patients, and that these levels increased as the severity of the disease increased. 13 Budzyn-Napierala et al, in their study examining LE activity, concentration, and AAT activity according to the clinical severity of the disease, indicated that LE activity decreased, particularly in the patient group with mild clinical symptoms, and that this decrease was associated with increased AAT activity. They believed that the LE-AAT balance might have turned in favor of antiprotease in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 98%